\(\sqrt{x}+y-2=\sqrt{x}+\sqrt{y}-\sqrt{2}\)

">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

7 tháng 10 2018

\(\frac{x+\left(\sqrt{x}-\sqrt{z}\right)^2}{y+\left(\sqrt{y}-\sqrt{z}\right)^2}=\frac{\left(\sqrt{x}+\sqrt{y}-\sqrt{z}\right)^2-y+\left(\sqrt{x}-\sqrt{z}\right)^2}{\left(\sqrt{x}+\sqrt{y}-\sqrt{z}\right)^2-x+\left(\sqrt{y}-\sqrt{z}\right)^2}\)

\(=\frac{\left(\sqrt{x}+2\sqrt{y}-\sqrt{z}\right)\left(\sqrt{x}-\sqrt{z}\right)+\left(\sqrt{x}-\sqrt{z}\right)^2}{\left(2\sqrt{x}+\sqrt{y}-\sqrt{z}\right)\left(\sqrt{y}-\sqrt{z}\right)+\left(\sqrt{y}-\sqrt{z}\right)^2}\)

\(=\frac{\left(\sqrt{x}-\sqrt{z}\right)\left(2\sqrt{x}+2\sqrt{y}-2\sqrt{z}\right)}{\left(\sqrt{y}-\sqrt{z}\right)\left(2\sqrt{x}+2\sqrt{y}-2\sqrt{z}\right)}\)

\(=\frac{\sqrt{x}-\sqrt{z}}{\sqrt{y}-\sqrt{z}}\)

a: \(=1-\left(\sqrt{x}\right)^3=1-x\sqrt{x}\)

b: \(=\left(\sqrt{x}\right)^3+2^3=x\sqrt{x}+8\)

c: \(=\left(\sqrt{x}\right)^3-\left(\sqrt{y}\right)^3=x\sqrt{x}-y\sqrt{y}\)

d: \(=x^3+\left(\sqrt{y}\right)^3=x^3+y\sqrt{y}\)

\(A,ĐKXĐ:x;y\ge0\)

\(A=\sqrt{xy}-2\sqrt{y}-5\sqrt{x}+10\)

\(=\sqrt{y}\left(\sqrt{x}-2\right)-5\left(\sqrt{x}-2\right)\)

\(=\left(\sqrt{x}-2\right)\left(\sqrt{y}-5\right)\)

\(ĐKXĐ:x;y\ge0\)

\(B=a\sqrt{x}+b\sqrt{y}-\sqrt{xy}-ab\)

\(=\left(a\sqrt{x}-\sqrt{xy}\right)+\left(b\sqrt{y}-ab\right)\)

\(=\sqrt{x}\left(a-\sqrt{y}\right)+b\left(\sqrt{y}-a\right)\)

\(=\sqrt{x}\left(a-\sqrt{y}\right)-b\left(a-\sqrt{y}\right)\)

\(=\sqrt{x}\left(a-\sqrt{y}\right)-b\left(a-\sqrt{y}\right)\)

\(=\left(a-\sqrt{y}\right)\left(\sqrt{x}-b\right)\)